Behavioural alterations induced by chronic exposure to 10 nm silicon dioxide nanoparticles - Bashir Jarrar; Amin Al‐Doaiss; Ali Shati; Mohammed Al‐Kahtani; Qais Jarrar (IET Nanobiotechnology)
Abstract Silicon dioxide nanoparticles (SiO2 NPs) are widely invested in medicine, industry, agriculture, consuming products, optical imaging agents, cosmetics, and drug delivery. However, the toxicity of these NPs on human health and the ecosystem have not been extensively studied and little information is available about their behavioural toxicities. The current study aimed to find out the behavioural alterations that might be induced by chronic exposure to 10 nm SiO2 NPs. BALB/C mice were subjected to 36 injections of SiO2 NPs (2 mg/kg Bw) and subjected to 11 neurobehavioural tests: elevated plus‐maze test, elevated zero‐maze test, multiradial maze test, open field test, hole‐board test, light‐dark box test, forced swimming test, tail‐suspension test, Morris water‐maze test, Y‐maze test and multiple T‐maze test. Treated mice demonstrated anxiety‐like effect, depression tendency, behavioural despair stress, exploration and locomotors activity reduction with error induction in both reference and working memories. The findings may suggest that silica NPs are anxiogenic and could aggravate depression affecting memory, learning, overall activity and exploratory behaviour. Moreover, the findings may indicate that these nanomaterials (NMs) may induce potential oxidative stress in the body leading to neurobehavioural alterations with possible changes in the vital organ including the central nervous system.